Donate your mobile phone (Journal of Parents and Teachers, 2013)
The author presents a Project promoted by Cruz Roja and Entreculturas, a recycling campaign for reusing second hand mobile phones. It reflects the objectives of the campaign, the place, the students, the development and a series of suggestions.
Keywords: Activities; mobile phone; campaign; Cruz Roja; Entreculturas; opinion; education.